(untitled) (Praxis Educativa, 2022)
This paper provides a view on the appropriation of Information and Communication Technologies (ICT’s) from the perspective of digital contents. The methodology was aimed at identifying trends in the use of ICT’s, through the application of a survey type instrument (Likert), answered by 404 teachers. Practices in the use of ICT’s, criteria for choosing content, methodological strategies and training in the use and development of content were consulted. The results show a discursive gap between the importance given to ICT’s and the teaching practices. It was identified that the respondents have been using the same tools for the past two decades. Besides, there is little implementation of educational innovation projects in their teaching. Likewise, ICT’s are assumed as a support for face-to-face teaching and teachers are more consumers than content producers. These findings contrast with the acceleration of the appropriation of ICT’s caused by the Covid-19 pandemic.